2022
DOI: 10.3390/s22051992
|View full text |Cite
|
Sign up to set email alerts
|

Missing and Corrupted Data Recovery in Wireless Sensor Networks Based on Weighted Robust Principal Component Analysis

Abstract: Although wireless sensor networks (WSNs) have been widely used, the existence of data loss and corruption caused by poor network conditions, sensor bandwidth, and node failure during transmission greatly affects the credibility of monitoring data. To solve this problem, this paper proposes a weighted robust principal component analysis method to recover the corrupted and missing data in WSNs. By decomposing the original data into a low-rank normal data matrix and a sparse abnormal matrix, the proposed method c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Recent studies have suggested different shrinkages of singular values based on their importance, which is a potential approach for improving data imputation processes [13]. However, a limited number of studies in the literature have exploited this approach for IoTs.…”
Section: Primary Challenges In 5g-enabled Iotsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have suggested different shrinkages of singular values based on their importance, which is a potential approach for improving data imputation processes [13]. However, a limited number of studies in the literature have exploited this approach for IoTs.…”
Section: Primary Challenges In 5g-enabled Iotsmentioning
confidence: 99%
“…In practice, the challenges associated with data reconstruction are often complex and involve various forms of corruption, including multiple types of noise, outliers, and missing values. However, previous studies mainly focused on individual types of corruption [11,13]. The corruption of IoT data can occur owing to various factors, including noise, outliers, and missing values.…”
Section: Introductionmentioning
confidence: 99%
“…For two-dimensional data such as matrix, the low-rank matrix approximate technique is a common choice due to its strong global constraint and strong ability to induce two-dimensional sparse. The Robust Principal Component Analysis (RPCA), whose essence is to use a low-rank constraint to approximate clean data and a sparse regular constraint to eliminate possible noise, has been widely used in background modeling, video, and image signals recovery, et al [4]. However, the RPCA can only process the two-dimensional matrix data, many real-world data like RGB color images and videos, naturally exist in multidimensional array forms (also referred to as tensors).…”
Section: Introductionmentioning
confidence: 99%
“…These nodes are responsible for capturing various forms of multimedia information and facilitating its transmission. However, due to the limited transmission range of each sensor node and the unpredictable wireless channel conditions, data loss and packet errors are common in WMSNs [2].…”
Section: Introductionmentioning
confidence: 99%